2007
DOI: 10.1177/097380100600100104
|View full text |Cite
|
Sign up to set email alerts
|

CO2Emission Reduction Strategies and Economic Development of India

Abstract: This article examines the consequences of alternative CO 2 emission reduction strategies on economic development and, in particular, the implications for the poor by empirically implementing an economy-wide model for India over a 35-year time horizon. A multisectoral, inter-temporal model in the activity analysis framework is used for this purpose. The model with specifi c technological alternatives, endogenous income distribution and truly dynamic behaviour and that covers the whole economy is an integrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Fisher-Vanden et al (1997) used a CGE model to compare the impacts of these two policies on GDP, and found that tradable permits are preferable to carbon taxes. Murthy et al (2007) used an activity-analysis-based model with endogenous determination of income distribution and poverty ratio. Incidentally, the CGE model of Fisher-Vanden et al (1997) is based on the assumption of a single representative household.…”
Section: The Energy and Emissions Scene In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Fisher-Vanden et al (1997) used a CGE model to compare the impacts of these two policies on GDP, and found that tradable permits are preferable to carbon taxes. Murthy et al (2007) used an activity-analysis-based model with endogenous determination of income distribution and poverty ratio. Incidentally, the CGE model of Fisher-Vanden et al (1997) is based on the assumption of a single representative household.…”
Section: The Energy and Emissions Scene In Indiamentioning
confidence: 99%
“…In a comparison of the two types of schemes for emission permits -the grandfathered emissions allocation scheme in which permits are allocated on the basis of 1990 emissions, and the equal per capita emission permits allocation scheme -they found the latter to be more beneficial for India. However, Murthy et al (2007) did not analyze the impact of a domestic carbon tax as their model is not price driven. Hence, it does not reflect the impact of carbon taxes on income distribution or the poverty ratio.…”
Section: The Energy and Emissions Scene In Indiamentioning
confidence: 99%
“…However, this has significant impacts on growth and welfare. In the case of India, Murthy et al (2006) estimate that as the emission restriction level is tightened from 10% to 20% and further to 30%, the effects on long run GDP and welfare become increasingly adverse. GDP falls by 0.53%, 1.36% and 4.06% and the number of poor increases by 2.1%, 5.9% and 17.5%, in the 30th year for 10%, 20% and 30% cumulative carbon emission restrictions, respectively.…”
Section: Intensity Targets For Developing Country Participationmentioning
confidence: 97%
“…Bussolo and O'Connor (2001) use a single country model for India to assess impacts of climate policy on four different regions within India taking into account ancillary benefits of CO 2 reduction. In more recent studies, Murthy et al (2007) with an activity analysis model and Ojha (2009) with a CGE model analyze the impact of Indian climate policy on poverty. Both models include different household types.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer-Vanden et al (1997) take international carbon prices from independent global studies, while Ojha (2009) assumes a fixed price of US$ 10 or 20 throughout the model period. Murthy et al (2007) compute the necessary monetary inflow to compensate for the welfare loss of domestic climate policy, so no assumption on international regimes or carbon prices is needed.…”
Section: Introductionmentioning
confidence: 99%